2005
DOI: 10.1016/j.jpeds.2005.04.065
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Exercise on Overnight Glycemic Control in Children with Type 1 Diabetes Mellitus

Abstract: These findings indicate that overnight hypoglycemia after exercise is common in children with T1DM and support the importance of modifying diabetes management after afternoon exercise to reduce the risk of hypoglycemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(62 citation statements)
references
References 22 publications
1
59
0
2
Order By: Relevance
“…2527 Problem solving may have a role in engagement in exercise since it requires consideration of numerous factors including the frequency, duration, type, and intensity of exercise, the adolescent’s current metabolic control and fitness level, type, timing, and dose of insulin delivered before exercise, site of injection, and food intake relative to exercise. 28,29 Identifying ways to engage in physical activity and healthy lifestyle also has implications for weight management and prevention in adolescents with T1DM. The results of this study suggest a need for more education and support pertaining to problem solving around exercise.…”
Section: Discussionmentioning
confidence: 99%
“…2527 Problem solving may have a role in engagement in exercise since it requires consideration of numerous factors including the frequency, duration, type, and intensity of exercise, the adolescent’s current metabolic control and fitness level, type, timing, and dose of insulin delivered before exercise, site of injection, and food intake relative to exercise. 28,29 Identifying ways to engage in physical activity and healthy lifestyle also has implications for weight management and prevention in adolescents with T1DM. The results of this study suggest a need for more education and support pertaining to problem solving around exercise.…”
Section: Discussionmentioning
confidence: 99%
“…For insulin-treated patients, exercise increases the risk of hypoglycemia. This risk may either be immediate, meaning during or shortly after exercise, or delayed by 6-15 hours after activity 38,39. Alcohol consumption can cause prolonged, unexpected hypoglycemia in people with T2DM, particularly in those taking ADA 40.…”
Section: Overviewmentioning
confidence: 99%
“…These findings concur with previous work by Tsalikian et al. (2005) who reported that during 60 min of MIE, 82% of participants experienced at least a 25% decrease in glucose compared to pre‐exercise. Conversely, previous research in adults with T1D showed less of a decline in blood glucose following sprint interval exercise, compared to MIE (Guelfi et al.…”
Section: Discussionmentioning
confidence: 99%
“…This increased incidence of nocturnal hypoglycemia has been demonstrated previously in children with T1D (aged 11–17 years), with 22% of participants experiencing hypoglycemia the night following 60 min of afternoon MIE (Tsalikian et al. 2005). The risk of nocturnal hypoglycemia after HIIE in youth with T1D is poorly understood, but is likely due to HIIE having greater insulin sensitizing effects than MIE (Cockcroft et al.…”
Section: Discussionmentioning
confidence: 99%